Francis Turbine Blade Design on the Basis of Port Area and Loss Analysis - Zhenmu Chen; Patrick M. Singh; Young-Do Choi (Energies, 2016)
In this study, a Francis turbine with specific speed of 130 m-kW was designed on the basis of the port area and loss analysis. The meridional shape of the runner was designed focusing mainly on the combination of the guide vane loss analysis and experience. The runner blade inlet and outlet angles were designed by calculation of Euler’s head, while the port area of blade was modified by keeping constant angles of the blade at inlet and outlet. The results show that the effect of the port area of runner blade on the flow exit angle from runner passage is significant. A correct flow exit angle reduces the energy loss at the draft tube, thereby improving the efficiency of the turbine. The best efficiency of 92.6% is achieved by this method, which is also similar to the design conditions by the one dimension loss analysis.